Potential earliest record of podocnemidoid turtles from the Early Cretaceous (Valanginian) of Colombia (2011)
A costal and a peripheral bone from the Early Cretaceous (Valanginian, ca. 135 Ma) Rosablanca Formation, Zapatoca town, Colombia are described. These specimens represent the earliest record of podocnemidoid turtles. Evolutionary and paleogeographical implications are also discussed.